Weather-resistant high-temperature polyether-based tpu robot cable

CN122762379APending Publication Date: 2026-09-15SHENZHEN RED BANNER ELECTRICIAN CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611198182.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-09-15

Smart Images

  • Figure CN122762379A_ABST
    Figure CN122762379A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of robot cables, and discloses a weather-resistant and high-temperature-resistant polyether-based TPU robot cable, which comprises a conductive core wire, an insulating layer wrapped outside the conductive core wire, and a sheath layer wrapped outside the insulating layer; the sheath layer takes polyether-based TPU as a base material, has a density of 1.25 g / cm 3 The surface-modified titanium dioxide / zinc oxide composite particles or the surface-modified cerium oxide particles and the antioxidant 1010 are dispersed in the sheath layer, and the mass ratio of the two is 1:2; the polymer molecular chains in the sheath layer are arranged in the axial direction of the cable and form a three-dimensional network structure through the urethane bonds in the polyether-based TPU; the insulating layer is made of high-density polyethylene and is combined with the sheath layer through a co-extrusion process. The polyether-based TPU dense sheath, the synergistic modification of the surface-modified particles and the antioxidant 1010, and the co-extrusion traction and shaping improve the high-temperature resistance, ultraviolet resistance, ozone resistance and repeated bending resistance of the cable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of robot cable technology, and in particular to weather-resistant and high-temperature resistant polyether-based TPU robot cables. Background Technology

[0002] Currently, robot cables are mainly used in automated production lines, logistics sorting equipment, outdoor service robots, and industrial robotic arms. The cables bend, twist, and reciprocate synchronously with the robot's joints. Besides transmitting electrical energy or signals, these cables must withstand long-term exposure to high temperatures, ultraviolet radiation, ozone corrosion, and mechanical bending. The sheath layer, located on the outermost side of the cable, is in direct contact with the external environment; its material stability, density, and bending recovery capacity affect the cable's lifespan.

[0003] Regarding the aforementioned issues, existing robot cables typically employ a combined structure of conductive core wires, insulation layers, and an outer sheath. The conductive core wires transmit current or signals, the insulation layer covers the conductive core wires to isolate adjacent conductors and maintain electrical safety, and the outer sheath covers the insulation layer to withstand friction, bending, and environmental forces. Some cables incorporate UV-absorbing or antioxidant components into the sheath material to reduce changes in material properties under light and heat-oxidation conditions; other solutions enhance environmental protection capabilities by increasing sheath thickness or employing multi-layered outer sheath structures.

[0004] While the aforementioned robot cables can meet conventional usage requirements under single environmental conditions, the performance degradation of the sheath layer accelerates under simultaneous exposure to high temperature, ultraviolet radiation, ozone, and repeated bending. Ordinary PVC or TPU sheaths are prone to enhanced chain segment movement and decreased mechanical properties at high temperatures, and elongation decreases after long-term ultraviolet irradiation. If large micropores exist within the sheath layer, ozone and oxygen can easily penetrate the material, causing further aging. Unmodified inorganic particles tend to agglomerate within the sheath material, and localized stress concentration can affect bending durability. Existing sheath materials also rarely simultaneously control particle surface modification, antioxidant ratios, sheath layer density, micropore diameter, and axial traction shaping, making it difficult for cables to simultaneously achieve high temperature resistance, ultraviolet resistance, ozone resistance, and resistance to repeated bending of robot joints. Summary of the Invention

[0005] The purpose of this invention is to provide a weather-resistant and high-temperature resistant polyether-based TPU robot cable, which solves the problem that the sheath layer of existing robot cables is prone to aging and cracking under the combined effects of high temperature, ultraviolet radiation, ozone, and repeated bending, making it difficult to simultaneously achieve high temperature resistance, weather resistance, ozone resistance, and bending resistance.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solution:

[0007] This invention provides a weather-resistant and high-temperature-resistant polyether-based TPU robot cable, employing the following technical solution:

[0008] A weather-resistant and high-temperature resistant polyether-based TPU robot cable includes a conductive core wire, an insulation layer covering the conductive core wire, and a sheath layer covering the insulation layer.

[0009] The sheath layer uses polyether-based TPU as the substrate, and the density of the sheath layer is 1.25 g / cm³. 3 above;

[0010] The sheath layer contains surface-modified titanium dioxide / zinc oxide composite particles or surface-modified cerium oxide particles, as well as antioxidant 1010, wherein the mass ratio of the surface-modified titanium dioxide / zinc oxide composite particles or surface-modified cerium oxide particles to the antioxidant 1010 is 1:2.

[0011] The molecular chains of polyether-based TPU in the sheath layer are oriented along the cable axis and form a three-dimensional network structure through the urethane bonds contained in the polyether-based TPU itself.

[0012] The insulation layer is made of high-density polyethylene, and the insulation layer and the sheath layer are bonded together by a co-extrusion process.

[0013] By adopting the above technical solution, the conductive core wire undertakes the function of transmitting electrical energy or signals, the insulation layer provides electrical insulation protection for the conductive core wire, and the sheath layer, as the outer layer of the cable, directly withstands high temperature, ultraviolet radiation, ozone corrosion, and bending stress. The sheath layer uses polyether-based TPU as the substrate, which can meet the requirements of robot cables for flexibility, hydrolysis resistance, and repeated bending performance. The density of the sheath layer is controlled to reach 1.25 g / cm³. 3 In addition, reducing the micropore size inside the sheath layer can reduce the diffusion channels of ozone, oxygen and water vapor in the sheath layer, thereby reducing the aging rate of the sheath layer.

[0014] Adding surface-modified titanium dioxide / zinc oxide composite particles or surface-modified cerium oxide particles to the sheath layer disperses these particles within the polyether-based TPU, improving the sheath layer's resistance to UV irradiation. Antioxidant 1010 is added to the aforementioned surface-modified particles at a 1:2 mass ratio, ensuring the sheath layer maintains good mechanical properties under UV irradiation and thermo-oxidative conditions. The surface-modified particles primarily reduce the impact of UV irradiation on the polyether-based TPU molecular chains, while antioxidant 1010 primarily improves the stability of the polyether-based TPU in thermo-oxidative environments. The combined effect reduces the elongation and tensile strength degradation of the sheath layer under high-temperature and outdoor conditions.

[0015] After the molecular chains of the polyether-based TPU in the sheath layer are oriented along the cable axis, the axial tensile and compressive deformation borne by the sheath layer during the bending process of the robot joint can be dispersed along the cable length, reducing local stress concentration. The urethane bonds contained in the polyether-based TPU itself participate in the formation of a three-dimensional network structure, enabling the sheath layer to maintain structural integrity under high-temperature environments and repeated bending conditions. The insulation layer is made of high-density polyethylene and is bonded to the sheath layer through a co-extrusion process, reducing the risk of interface separation and forming a continuous cable structure of conductive core, insulation layer, and sheath layer.

[0016] Preferably, the surface-modified titanium dioxide / zinc oxide composite particles are prepared from nano-titanium dioxide, nano-zinc oxide and γ-aminopropyltriethoxysilane.

[0017] By employing the above technical solution, γ-aminopropyltriethoxysilane undergoes hydrolysis under ethanol aqueous solution and acidic conditions, and combines with the active groups on the surfaces of nano-titanium dioxide and nano-zinc oxide, forming a silane-modified layer on the surfaces of nano-titanium dioxide and nano-zinc oxide. After surface modification, the dispersibility of nanoparticles in polyether-based TPU is improved, and particle agglomeration is reduced, which is beneficial to improving the UV aging resistance and ozone barrier performance of the sheath layer.

[0018] Preferably, the mass ratio of the nano-titanium dioxide to the nano-zinc oxide is 40:60 to 60:40.

[0019] By adopting the above technical solution, the composite particles of nano-titanium dioxide and nano-zinc oxide, compounded at the aforementioned mass ratio, can maintain a good dispersion state within the sheath layer, while simultaneously achieving particle filling, UV shielding, and sheath layer densification effects. If the ratio of nano-titanium dioxide to nano-zinc oxide deviates significantly from the above range, the uniformity of particle dispersion and the overall performance of the sheath layer will be affected.

[0020] Preferably, the surface-modified cerium oxide particles are prepared from nano-cerium oxide and γ-aminopropyltriethoxysilane.

[0021] By adopting the above technical solution, nano-cerium oxide, after surface modification with γ-aminopropyltriethoxysilane, can be added to the sheath layer as a substitute for surface-modified titanium dioxide / zinc oxide composite particles. After dispersion in polyether-based TPU, the surface-modified cerium oxide particles can improve the stability of the sheath layer under ultraviolet irradiation and ozone conditions, while maintaining the flexibility of the sheath layer.

[0022] Preferably, the average particle size of the surface-modified titanium dioxide / zinc oxide composite particles or the surface-modified cerium oxide particles is less than 100 nm.

[0023] By adopting the above technical solution, after controlling the average particle size of the surface-modified particles to less than 100 nm, the particles can form a more uniform dispersion system in polyether-based TPU, reducing stress concentration caused by large-diameter particles. This particle size range is beneficial for maintaining the tensile and flexural properties of the sheath layer and improving its resistance to ultraviolet radiation and ozone penetration.

[0024] Preferably, the amount of antioxidant 1010 added is 0.5% to 1% of the mass of the polyether-based TPU.

[0025] By adopting the above technical solution, when the amount of antioxidant 1010 added is controlled at 0.5% to 1%, the thermo-oxidative stability of the sheath layer can be improved, and the decrease in tensile strength after thermal aging can be reduced. When the amount added is below this range, the thermo-oxidative stability of the sheath layer is insufficient; when the amount added is above this range, the processing fluidity and mechanical properties of the sheath layer will be affected.

[0026] Preferably, the sheath layer has micropores with a diameter of less than 50 nm.

[0027] By adopting the above technical solution, the sheath layer has micropores, and when the diameter of the micropores is reduced to less than 50 nm, the diffusion paths of ozone, oxygen, and water vapor in the sheath layer are restricted, thus reducing the ozone permeability of the sheath layer. The combined effect of micropore diameter control and sheath layer density control enables the sheath layer to maintain good weather resistance in outdoor or industrial high-temperature environments.

[0028] Preferably, the sheath layer is prepared by the following steps: based on 100 parts by weight of the polyether-based TPU, 0.25 to 0.50 parts by weight of the surface-modified titanium dioxide / zinc oxide composite particles or the surface-modified cerium oxide particles, and 0.50 to 1.00 parts by weight of the antioxidant 1010 are added, and the mixture is extruded using a two-stage screw extruder, wherein the temperature of the first zone is 180 to 190°C, the temperature of the second zone is 160 to 170°C, and the die pressure is 8 to 10 MPa.

[0029] By adopting the above technical solution, the polyether-based TPU, the surface-modified titanium dioxide / zinc oxide composite particles or the surface-modified cerium oxide particles, and the antioxidant 1010 are first mixed, allowing the surface-modified particles and antioxidant 1010 to enter the polyether-based TPU matrix. The temperature of the first zone of the two-stage screw extruder is controlled at 180-190℃ to plasticize the polyether-based TPU; the temperature of the second zone is controlled at 160-170℃ to reduce melt viscosity and improve melt stability; the die pressure is controlled at 8-10 MPa to form a dense structure in the sheath layer during extrusion. Under the above extrusion conditions, the sheath layer density reaches 1.25 g / cm³. 3The above applies to the sheath layer, which has micropores with a diameter of less than 50 nm.

[0030] Preferably, after extrusion, the sheath layer is traction-shaped along the cable axis at a traction ratio of 1.05 to 1.20, so that the molecular chains of polyether-based TPU in the sheath layer are oriented along the cable axis.

[0031] By adopting the above technical solution, when the traction ratio is controlled between 1.05 and 1.20, the sheath layer develops a moderate axial orientation before cooling and setting, causing the molecular chains of the polyether-based TPU in the sheath layer to align along the cable axis. This axial orientation helps improve the cable's fatigue resistance during robot joint bending and reduces the risk of cracking in the sheath layer during repeated bending.

[0032] Preferably, the conductive core wire is formed by stranding multiple annealed copper wires, wherein the diameter of a single strand of the multiple annealed copper wire is 0.08 to 0.15 mm, and the stranding pitch is 8 to 14 times the outer diameter of the conductive core wire.

[0033] By adopting the above technical solution, the conductive core wire formed by stranding multiple annealed copper wires has good bending flexibility. With the diameter of each annealed copper wire controlled at 0.08–0.15 mm and the stranding pitch controlled at 8–14 times the outer diameter of the conductive core wire, the risk of single-wire breakage is reduced during repeated bending. Together with the external high-density polyethylene insulation layer and polyether-based TPU sheath layer, it meets the bending requirements of robot cables.

[0034] In summary, the present invention has at least one of the following beneficial technical effects:

[0035] 1. The weather-resistant and high-temperature resistant polyether-based TPU robot cable of the present invention adopts a composite structure of conductive core wire, insulation layer and sheath layer. The sheath layer is based on polyether-based TPU, and is combined with surface-modified inorganic particles and antioxidants, so that the sheath layer has good stability under high temperature, ultraviolet, ozone and repeated bending environment, thereby improving the weather resistance and service life of robot cable.

[0036] 2. This invention uses a two-stage screw extrusion process to densify the sheath layer and combines it with a traction shaping process to ensure that the polymer molecular chains in the sheath layer are arranged in an orderly manner along the cable axis. At the same time, the urethane bonds in the polyether-based TPU help to form a stable network structure, thereby reducing the penetration of media such as ozone and oxygen into the interior of the sheath layer and improving the structural stability of the sheath layer under high temperature and repeated bending conditions.

[0037] 3. The insulation layer of this invention is made of high-density polyethylene and is combined with the sheath layer through a co-extrusion process, which reduces the risk of interlayer separation between the insulation layer and the sheath layer while maintaining good insulation performance. It is suitable for application scenarios such as automated production lines, logistics sorting systems, outdoor service robots, and robot cables in high-temperature industrial environments. Attached Figure Description

[0038] Figure 1 This is a cross-sectional schematic diagram of the weather-resistant and high-temperature-resistant polyether-based TPU robot cable of the present invention;

[0039] Figure 2 This is a bar chart showing the retention rate of tensile strength of the sheath layer after 125°C heat aging according to the present invention.

[0040] Figure 3 This is a bar chart showing the attenuation rate of the sheath layer elongation after 1000 hours of UV irradiation according to the present invention.

[0041] Figure 4 This is a line graph showing the ozone permeability of the sheath layer of the present invention.

[0042] Figure 5 This is a bar chart showing the number of joint bending cycles of the robot according to the present invention.

[0043] The components are: 1. Conductive core wire; 2. Insulation layer; 3. Sheath layer. Detailed Implementation

[0044] To enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are merely some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0045] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.

[0046] Polyether-based TPU is a polyether-type thermoplastic polyurethane elastomer, belonging to a linear segmented block copolymer. The soft segment is composed of polytetramethylene ether glycol segments with repeating units of —O—(CH2)4—, while the hard segment is formed by the reaction of 4,4′-diphenylmethane diisocyanate and 1,4-butanediol. The main chain contains urethane bonds. Its number-average molecular weight is 90,000–140,000, weight-average molecular weight is 180,000–350,000, molecular weight distribution is 2.0–2.8, Shore hardness is 85A–92A, melt index is 10–18 g / 10min (190℃, 2.16 kg), and substrate density is 1.20–1.24 g / cm³. 3 The polyether-based TPU was used to prepare the sheath layer 3. After surface modification with titanium dioxide / zinc oxide composite particles or surface modification with cerium oxide particles, antioxidant 1010, and densification extrusion treatment, the density of the sheath layer 3 reached 1.25 g / cm³. 3 above.

[0047] High-density polyethylene, CAS No.: 9002-88-4, repeating unit: —CH2—CH2—, density: 0.945~0.965g / cm³ 3 A melt flow index of 0.3–1.0 g / 10 min (190 °C, 2.16 kg) was used to prepare insulating layer 2.

[0048] Titanium dioxide, CAS No.: 13463-67-7, molecular formula TiO2, is selected as anatase nano titanium dioxide with an average particle size of 20-60nm. It is used to form surface-modified titanium dioxide / zinc oxide composite particles after being compounded with zinc oxide and surface modified.

[0049] Zinc oxide, CAS No.: 1314-13-2, with the molecular formula ZnO and an average particle size of 20-60 nm, is used to form surface-modified titanium dioxide / zinc oxide composite particles after being compounded with titanium dioxide and surface modified.

[0050] Cerium oxide, CAS No.: 1306-38-3, with the molecular formula CeO2 and an average particle size of 30-80 nm, is used to form surface-modified cerium oxide particles after surface modification.

[0051] Antioxidant 1010, chemically named pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionic acid], CAS number: 6683-19-8, molecular formula: C 73 H 108 O 12 It is used to improve the thermo-oxidative stability and UV aging stability of the sheath layer 3.

[0052] γ-aminopropyltriethoxysilane, CAS No.: 919-30-2, molecular formula: C9H 23NO3Si is used to prepare surface-modified titanium dioxide / zinc oxide composite particles or surface-modified cerium oxide particles.

[0053] The conductive core wire 1 is formed by stranding multiple annealed copper wires. The diameter of a single strand of the multiple annealed copper wire is 0.08 to 0.15 mm, and the stranding pitch is 8 to 14 times the outer diameter of the conductive core wire 1.

[0054] Anhydrous ethanol, glacial acetic acid, and deionized water were used to prepare surface-modified titanium dioxide / zinc oxide composite particles or surface-modified cerium oxide particles.

[0055] Preparation Example 1:

[0056] This preparation example provides a method for preparing surface-modified titanium dioxide / zinc oxide composite particles. The surface-modified titanium dioxide / zinc oxide composite particles are prepared from nano-titanium dioxide, nano-zinc oxide, and γ-aminopropyltriethoxysilane, including the following steps:

[0057] (1) Weigh 50 parts by mass of nano titanium dioxide and 50 parts by mass of nano zinc oxide. The mass ratio of nano titanium dioxide to nano zinc oxide is 50:50. Add nano titanium dioxide and nano zinc oxide to an ethanol aqueous solution with a mass fraction of 75%. Control the solid content to 10%. Use a high-speed disperser to disperse at 1200 r / min for 20 min to obtain an inorganic particle dispersion.

[0058] (2) Add glacial acetic acid to the inorganic particle dispersion to adjust the pH of the system to 4.5, add 2.0 parts by mass of γ-aminopropyltriethoxysilane, and stir the reaction at 50°C for 2 hours.

[0059] (3) After the reaction was completed, the reaction solution was centrifuged and the resulting solid was washed three times with anhydrous ethanol and then dried at 80°C for 8 hours. Subsequently, it was subjected to air jet milling to obtain surface-modified titanium dioxide / zinc oxide composite particles. The average particle size of the obtained surface-modified titanium dioxide / zinc oxide composite particles was 62 nm, and the average particle size was less than 100 nm.

[0060] Preparation Example 2:

[0061] This preparation example provides a method for preparing surface-modified titanium dioxide / zinc oxide composite particles. The surface-modified titanium dioxide / zinc oxide composite particles are prepared from nano-titanium dioxide, nano-zinc oxide, and γ-aminopropyltriethoxysilane, including the following steps:

[0062] (1) Weigh 60 parts by mass of nano titanium dioxide and 40 parts by mass of nano zinc oxide. The mass ratio of nano titanium dioxide to nano zinc oxide is 60:40. Add nano titanium dioxide and nano zinc oxide to an ethanol aqueous solution with a mass fraction of 70% and control the solid content to 8%. Use a high-speed disperser to disperse at 1000 r / min for 15 min to obtain an inorganic particle dispersion.

[0063] (2) Add glacial acetic acid to the inorganic particle dispersion to adjust the pH of the system to 4.2, add 1.0 part by mass of γ-aminopropyltriethoxysilane, and stir the reaction at 40°C for 1 h.

[0064] (3) After the reaction was completed, the reaction solution was centrifuged and the resulting solid was washed three times with anhydrous ethanol and then dried at 75°C for 7 hours. Subsequently, it was subjected to air jet milling to obtain surface-modified titanium dioxide / zinc oxide composite particles. The average particle size of the obtained surface-modified titanium dioxide / zinc oxide composite particles was 73 nm, and the average particle size was less than 100 nm.

[0065] Preparation Example 3:

[0066] This preparation example provides a method for preparing surface-modified titanium dioxide / zinc oxide composite particles. The surface-modified titanium dioxide / zinc oxide composite particles are prepared from nano-titanium dioxide, nano-zinc oxide, and γ-aminopropyltriethoxysilane, including the following steps:

[0067] (1) Weigh 40 parts by mass of nano titanium dioxide and 60 parts by mass of nano zinc oxide. The mass ratio of nano titanium dioxide to nano zinc oxide is 40:60. Add nano titanium dioxide and nano zinc oxide to an 80% ethanol aqueous solution and control the solid content to 12%. Use a high-speed disperser to disperse at 1500 r / min for 30 min to obtain an inorganic particle dispersion.

[0068] (2) Add glacial acetic acid to the inorganic particle dispersion to adjust the pH of the system to 4.8, add 3.0 parts by mass of γ-aminopropyltriethoxysilane, and stir the reaction at 60°C for 3 hours.

[0069] (3) After the reaction was completed, the reaction solution was centrifuged, and the resulting solid was washed three times with anhydrous ethanol and then dried at 85°C for 9 hours. Subsequently, it was subjected to air jet milling to obtain surface-modified titanium dioxide / zinc oxide composite particles. The average particle size of the obtained surface-modified titanium dioxide / zinc oxide composite particles was 58 nm, and the average particle size was less than 100 nm.

[0070] Preparation Example 4:

[0071] This preparation example provides a method for preparing surface-modified cerium oxide particles, which are obtained from nano-cerium oxide and γ-aminopropyltriethoxysilane, including the following steps:

[0072] (1) Weigh 100 parts by mass of nano-cerium oxide, add nano-cerium oxide to an ethanol aqueous solution with a mass fraction of 75%, control the solid content to be 10%, and disperse it for 20 min at 1200 r / min using a high-speed disperser to obtain cerium oxide dispersion.

[0073] (2) Add glacial acetic acid to the cerium oxide dispersion to adjust the pH of the system to 4.5, add 2.0 parts by mass of γ-aminopropyltriethoxysilane, and stir the reaction at 50°C for 2 hours.

[0074] (3) After the reaction was completed, the reaction solution was centrifuged and the resulting solid was washed three times with anhydrous ethanol and then dried at 80°C for 8 hours. Subsequently, it was subjected to air jet milling to obtain surface-modified cerium oxide particles. The average particle size of the obtained surface-modified cerium oxide particles was 65 nm, and the average particle size was less than 100 nm.

[0075] Example 1:

[0076] This embodiment provides a weather-resistant and high-temperature-resistant polyether-based TPU robot cable, including the following steps:

[0077] (1) Dry polyether-based TPU at 80°C for 4 hours and high-density polyethylene at 75°C for 3 hours for later use.

[0078] (2) Based on 100 parts by mass of polyether-based TPU, add 0.375 parts by mass of the surface-modified titanium dioxide / zinc oxide composite particles obtained in Preparation Example 1, and 0.75 parts by mass of antioxidant 1010. The mass ratio of the surface-modified titanium dioxide / zinc oxide composite particles to antioxidant 1010 is 1:2, and in the sheath layer 3, the mass of antioxidant 1010 is 0.75% of the mass of polyether-based TPU. Add the above materials to a high-speed mixer and mix at 800 r / min for 8 min to obtain the sheath layer raw material.

[0079] (3) The conductive core wire 1 is formed by stranding multiple annealed copper wires. The diameter of each strand of the annealed copper wire is 0.12 mm, and the stranding pitch is 11 times the outer diameter of the conductive core wire 1. The conductive core wire 1 is placed at the unloading end of the co-extrusion production line, so that the conductive core wire 1 passes through the extrusion die of the insulation layer 2 and the extrusion die of the sheath layer 3 in sequence. After being melted by the first extruder, the high-density polyethylene is coated on the outside of the conductive core wire 1 to form the insulation layer 2.

[0080] (4) Add the sheath layer material to the two-stage screw extruder. The temperature of the first zone of the two-stage screw extruder is 185°C, the temperature of the second zone is 165°C, and the die pressure is 9MPa, so that the polyether-based TPU is fully plasticized and the melt viscosity is reduced.

[0081] (5) The sheath layer 3 is wrapped around the insulation layer 2 by co-extrusion process, and the insulation layer 2 and the sheath layer 3 are bonded by co-extrusion process. After the sheath layer 3 and the insulation layer 2 are co-extruded, they are traction-shaped along the axial direction of the weather-resistant and high-temperature resistant polyether-based TPU robot cable at a traction ratio of 1.12, so as to realize that the molecular chains of polyether-based TPU in the sheath layer 3 are oriented along the axial direction of the weather-resistant and high-temperature resistant polyether-based TPU robot cable, and form a three-dimensional network structure through the urethane bonds contained in the polyether-based TPU itself.

[0082] (6) After water cooling, air drying, and winding, the following is obtained: Figure 1 The weather-resistant and high-temperature-resistant polyether-based TPU robot cable shown is an example. The density of the resulting sheath layer 3 is 1.27 g / cm³. 3 The sheath layer 3 has micropores with a diameter of 38 nm, which is less than 50 nm.

[0083] Example 2:

[0084] This embodiment provides a weather-resistant and high-temperature-resistant polyether-based TPU robot cable, including the following steps:

[0085] (1) Dry polyether-based TPU at 80°C for 4 hours and high-density polyethylene at 75°C for 3 hours for later use.

[0086] (2) Based on 100 parts by mass of polyether-based TPU, add 0.25 parts by mass of the surface-modified titanium dioxide / zinc oxide composite particles obtained in Preparation Example 2, and 0.50 parts by mass of antioxidant 1010. The mass ratio of the surface-modified titanium dioxide / zinc oxide composite particles to antioxidant 1010 is 1:2, and in the sheath layer 3, the mass of antioxidant 1010 is 0.50% of the mass of polyether-based TPU. Add the above materials to a high-speed mixer and mix at 700 r / min for 6 min to obtain the sheath layer raw material.

[0087] (3) The conductive core wire 1 is formed by stranding multiple annealed copper wires. The diameter of each strand of the annealed copper wire is 0.08 mm, and the stranding pitch is 8 times the outer diameter of the conductive core wire 1. The conductive core wire 1 is placed at the unloading end of the co-extrusion production line, so that the conductive core wire 1 passes through the extrusion die of the insulation layer 2 and the extrusion die of the sheath layer 3 in sequence. After being melted by the first extruder, the high-density polyethylene is coated on the outside of the conductive core wire 1 to form the insulation layer 2.

[0088] (4) Add the sheath layer material to the two-stage screw extruder. The temperature of the first zone of the two-stage screw extruder is 180°C, the temperature of the second zone is 160°C, and the die pressure is 8MPa, so that the polyether-based TPU is plasticized and the melt viscosity is reduced.

[0089] (5) The sheath layer 3 is wrapped around the insulation layer 2 by co-extrusion process, and the insulation layer 2 and the sheath layer 3 are bonded by co-extrusion process. After the sheath layer 3 and the insulation layer 2 are co-extruded, they are traction-shaped along the axial direction of the weather-resistant and high-temperature resistant polyether-based TPU robot cable at a traction ratio of 1.05, so as to realize that the molecular chains of polyether-based TPU in the sheath layer 3 are oriented along the axial direction of the weather-resistant and high-temperature resistant polyether-based TPU robot cable, and form a three-dimensional network structure through the urethane bonds contained in the polyether-based TPU itself.

[0090] (6) After water cooling, air drying, and winding, the following is obtained: Figure 1 The weather-resistant and high-temperature-resistant polyether-based TPU robot cable shown is an example. The density of the resulting sheath layer 3 is 1.25 g / cm³. 3 The sheath layer 3 has micropores with a diameter of 46 nm, which is less than 50 nm.

[0091] Example 3:

[0092] This embodiment provides a weather-resistant and high-temperature-resistant polyether-based TPU robot cable, including the following steps:

[0093] (1) Dry polyether-based TPU at 80°C for 4 hours and high-density polyethylene at 75°C for 3 hours for later use.

[0094] (2) Based on 100 parts by mass of polyether-based TPU, add 0.50 parts by mass of the surface-modified titanium dioxide / zinc oxide composite particles obtained in Preparation Example 3, and 1.00 parts by mass of antioxidant 1010. The mass ratio of the surface-modified titanium dioxide / zinc oxide composite particles to antioxidant 1010 is 1:2, and in the sheath layer 3, the mass of antioxidant 1010 is 1.00% of the mass of polyether-based TPU. Add the above materials to a high-speed mixer and mix at 900 r / min for 10 min to obtain the sheath layer raw material.

[0095] (3) The conductive core wire 1 is formed by stranding multiple annealed copper wires. The diameter of each strand of the annealed copper wire is 0.15 mm, and the stranding pitch is 14 times the outer diameter of the conductive core wire 1. The conductive core wire 1 is placed at the unloading end of the co-extrusion production line, so that the conductive core wire 1 passes through the extrusion die of the insulation layer 2 and the extrusion die of the sheath layer 3 in sequence. After being melted by the first extruder, the high-density polyethylene is coated on the outside of the conductive core wire 1 to form the insulation layer 2.

[0096] (4) Add the sheath layer material to the two-stage screw extruder. The temperature of the first zone of the two-stage screw extruder is 190°C, the temperature of the second zone is 170°C, and the die pressure is 10MPa, so that the polyether-based TPU is plasticized and the melt viscosity is reduced.

[0097] (5) The sheath layer 3 is wrapped around the insulation layer 2 by co-extrusion process, and the insulation layer 2 and the sheath layer 3 are bonded by co-extrusion process. After the sheath layer 3 and the insulation layer 2 are co-extruded, they are traction-shaped along the axial direction of the weather-resistant and high-temperature resistant polyether-based TPU robot cable at a traction ratio of 1.20, so as to realize that the molecular chains of polyether-based TPU in the sheath layer 3 are oriented along the axial direction of the weather-resistant and high-temperature resistant polyether-based TPU robot cable, and form a three-dimensional network structure through the urethane bonds contained in the polyether-based TPU itself.

[0098] (6) After water cooling, air drying, and winding, the following is obtained: Figure 1 The weather-resistant and high-temperature-resistant polyether-based TPU robot cable shown is an example. The density of the resulting sheath layer 3 is 1.29 g / cm³. 3 The sheath layer 3 has micropores with a diameter of 32 nm, which is less than 50 nm.

[0099] Example 4:

[0100] This embodiment provides a weather-resistant and high-temperature-resistant polyether-based TPU robot cable, including the following steps:

[0101] (1) Dry polyether-based TPU at 80°C for 4 hours and high-density polyethylene at 75°C for 3 hours for later use.

[0102] (2) Based on 100 parts by mass of polyether-based TPU, add 0.375 parts by mass of the surface-modified cerium oxide particles obtained in Preparation Example 4 and 0.75 parts by mass of antioxidant 1010. The mass ratio of surface-modified cerium oxide particles to antioxidant 1010 is 1:2, and in the sheath layer 3, the mass of antioxidant 1010 is 0.75% of the mass of polyether-based TPU. Add the above materials to a high-speed mixer and mix at 800 r / min for 8 min to obtain the sheath layer raw material.

[0103] (3) The conductive core wire 1 is formed by stranding multiple annealed copper wires. The diameter of each strand of the annealed copper wire is 0.12 mm, and the stranding pitch is 11 times the outer diameter of the conductive core wire 1. The conductive core wire 1 is placed at the unloading end of the co-extrusion production line, so that the conductive core wire 1 passes through the extrusion die of the insulation layer 2 and the extrusion die of the sheath layer 3 in sequence. After being melted by the first extruder, the high-density polyethylene is coated on the outside of the conductive core wire 1 to form the insulation layer 2.

[0104] (4) Add the sheath layer material to the two-stage screw extruder. The temperature of the first zone of the two-stage screw extruder is 185°C, the temperature of the second zone is 165°C, and the die pressure is 9MPa, so that the polyether-based TPU is plasticized and the melt viscosity is reduced.

[0105] (5) The sheath layer 3 is wrapped around the insulation layer 2 by co-extrusion process, and the insulation layer 2 and the sheath layer 3 are bonded by co-extrusion process. After the sheath layer 3 and the insulation layer 2 are co-extruded, they are traction-shaped along the axial direction of the weather-resistant and high-temperature resistant polyether-based TPU robot cable at a traction ratio of 1.12, so as to realize that the molecular chains of polyether-based TPU in the sheath layer 3 are oriented along the axial direction of the weather-resistant and high-temperature resistant polyether-based TPU robot cable, and form a three-dimensional network structure through the urethane bonds contained in the polyether-based TPU itself.

[0106] (6) After water cooling, air drying, and winding, the following is obtained: Figure 1 The weather-resistant and high-temperature-resistant polyether-based TPU robot cable shown is an example. The density of the resulting sheath layer 3 is 1.26 g / cm³. 3 The sheath layer 3 has micropores with a diameter of 41 nm, which is less than 50 nm.

[0107] Comparative Example 1:

[0108] Compared with Example 1, the difference is that the sheath layer 3 uses ordinary polyester TPU instead of polyether-based TPU, and all other aspects are the same.

[0109] Comparative Example 2:

[0110] Compared with Example 1, the difference is that the surface-modified titanium dioxide / zinc oxide composite particles obtained in Preparation Example 1 are not added to the sheath layer 3, the amount of antioxidant 1010 is kept at 0.75 parts by mass, and the rest are the same.

[0111] Comparative Example 3:

[0112] Compared with Example 1, the difference is that antioxidant 1010 is not added to the sheath layer 3, and the amount of surface-modified titanium dioxide / zinc oxide composite particles obtained in Preparation Example 1 is kept at 0.375 parts by mass, while the rest are the same.

[0113] Comparative Example 4:

[0114] Compared with Example 1, the difference is that the amount of surface-modified titanium dioxide / zinc oxide composite particles obtained in Example 1 in the sheath layer 3 is 0.75 parts by mass, the amount of antioxidant 1010 is 0.375 parts by mass, the mass ratio of surface-modified titanium dioxide / zinc oxide composite particles to antioxidant 1010 is 2:1, and all other aspects are the same.

[0115] Comparative Example 5:

[0116] Compared with Example 1, the difference is that the sheath layer 3 uses unmodified titanium dioxide and zinc oxide mixed particles instead of the surface-modified titanium dioxide / zinc oxide composite particles obtained in Example 1. The mass ratio of titanium dioxide to zinc oxide is 1:1, and all other aspects are the same.

[0117] Comparative Example 6:

[0118] Compared with Example 1, the difference lies in that the temperature of the first zone during extrusion of the sheath layer 3 is 175°C, the temperature of the second zone is 175°C, the die pressure is 6MPa, and the density of the resulting sheath layer 3 is 1.18g / cm³. 3 The sheath layer 3 has micropores with a diameter of 84 nm, and the rest are the same.

[0119] Comparative Example 7:

[0120] Compared with Example 1, the difference is that the sheath layer 3 uses PVC material instead of polyether-based TPU, and the sheath layer raw materials composed of surface-modified titanium dioxide / zinc oxide composite particles and antioxidant 1010 obtained in Example 1 are the same.

[0121] Test Example 1:

[0122] This test case evaluates the ability of weather-resistant and high-temperature-resistant polyether-based TPU robot cables to retain their mechanical properties after thermal aging at 125°C, and includes the following steps:

[0123] (1) Take the cables prepared in Examples 1-4 and Comparative Examples 1-7 respectively, peel off the sheath layer 3 along the axial direction, and cut the sheath layer 3 into dumbbell-shaped samples.

[0124] (2) Five samples were taken from each group. One group was placed in an environment of 23℃ and 50% relative humidity for 24 hours and the initial tensile strength was tested. The other group was placed in a 125℃ heat aging chamber for 168 hours. After taking it out, it was placed in an environment of 23℃ and 50% relative humidity for 24 hours and the tensile strength after heat aging was tested.

[0125] (3) Tensile tests were performed using an electronic universal testing machine at a tensile speed of 250 mm / min.

[0126] (4) Calculate the tensile strength retention rate according to the following formula: tensile strength retention rate = tensile strength after heat aging / initial tensile strength × 100%.

[0127] Table 1. Test results of tensile strength retention rate of sheath layer 3 after heat aging at 125℃

[0128] sample Initial tensile strength (MPa) Tensile strength (MPa) after heat aging Tensile strength retention rate (%) Example 1 39.8 29.3 73.6 Example 2 38.5 27.6 71.7 Example 3 40.6 30.9 76.1 Example 4 39.1 27.8 71.1 Comparative Example 1 35.7 18.6 52.1 Comparative Example 2 38.9 24.8 63.8 Comparative Example 3 39.3 22.5 57.3 Comparative Example 4 39.6 25.1 63.4 Comparative Example 5 38.7 24.2 62.5 Comparative Example 6 37.4 21.7 58.0 Comparative Example 7 31.2 14.9 47.8

[0129] in conclusion:

[0130] According to the data in Table 1, the tensile strength retention rates of Examples 1–4 after heat aging at 125℃ for 168 hours were 71.1%–76.1%, with Example 1 showing an increase of approximately 41.3% in tensile strength retention compared to Comparative Example 1. This result indicates that the sheath layer 3 formed by polyether-based TPU exhibits good molecular chain stability at high temperatures. The surface-modified titanium dioxide / zinc oxide composite particles or surface-modified cerium oxide particles, together with antioxidant 1010, reduced chain segment breakage caused by thermo-oxidative aging. Comparative Example 3, which did not include antioxidant 1010, showed a significant decrease in tensile strength retention rate after heat aging. In Comparative Example 6, the sheath layer 3 had insufficient density and a large micropore diameter, resulting in a lower tensile strength retention rate than Example 1. This suggests that the second-stage screw extrusion temperature and die pressure affect the densification and high-temperature stability of the sheath layer 3.

[0131] according to Figure 2 The bar chart showing the retention rate of tensile strength of sheath layer 3 after 125℃ heat aging shows that the height of the bars in Examples 1 to 4 is generally higher than that in Comparative Examples 1 to 7, with Example 3 having the highest retention rate and Comparative Example 7 having the lowest. Figure 2 It can intuitively reflect the synergistic contribution of polyether-based TPU, surface-modified titanium dioxide / zinc oxide composite particles or surface-modified cerium oxide particles, antioxidant 1010 and densification extrusion process to the high temperature resistance of sheath layer 3.

[0132] Test Example 2:

[0133] This test case evaluates the elongation degradation of weather-resistant and high-temperature-resistant polyether-based TPU robot cables after ultraviolet irradiation, and includes the following steps:

[0134] (1) Take the cables prepared in Examples 1-4 and Comparative Examples 1-7 respectively, peel off the sheath layer 3 along the axial direction, and cut the sheath layer 3 into dumbbell-shaped samples.

[0135] (2) Test the initial elongation at break of each specimen.

[0136] (3) Place the sample in an ultraviolet aging test chamber, use UVA-340 lamp tube, cover the irradiation band of 290~400nm, control the black panel temperature at 60℃, and the cumulative irradiation time is 1000h.

[0137] (4) After the UV irradiation is completed, the sample is placed in an environment of 23°C and 50% relative humidity for 24 hours, and the elongation at break after UV irradiation is tested.

[0138] (5) Calculate the elongation decay rate according to the following formula: Elongation decay rate = (initial breaking elongation - breaking elongation after UV irradiation) / initial breaking elongation × 100%.

[0139] Table 2. Results of elongation attenuation test of sheath layer 3 after 1000 hours of UV irradiation

[0140] sample Initial elongation at break (%) Elongation at break (%) after UV irradiation Elongation attenuation rate (%) Example 1 518 466 10.0 Example 2 505 444 12.1 Example 3 522 457 12.5 Example 4 498 431 13.5 Comparative Example 1 468 341 27.1 Comparative Example 2 513 373 27.3 Comparative Example 3 516 408 20.9 Comparative Example 4 509 402 21.0 Comparative Example 5 506 386 23.7 Comparative Example 6 487 358 26.5 Comparative Example 7 392 236 39.8

[0141] in conclusion:

[0142] According to the data in Table 2, the elongation attenuation rate of Examples 1-4 after 1000 hours of UV irradiation did not exceed 15%, meeting the requirements for long-term outdoor weather resistance of the sheath layer 3. Comparative Example 2, without the addition of surface-modified titanium dioxide / zinc oxide composite particles, achieved an elongation attenuation rate of 27.3%, indicating that the surface-modified titanium dioxide / zinc oxide composite particles have a shielding effect against ultraviolet rays in the 290-400nm wavelength band. Comparative Example 5, using a mixture of unmodified titanium dioxide and zinc oxide particles, showed a higher elongation attenuation rate than Example 1, indicating that surface modification treatment improved the dispersion stability of inorganic particles in polyether-based TPU. In Comparative Example 4, changing the mass ratio of surface-modified titanium dioxide / zinc oxide composite particles to antioxidant 1010 increased the elongation attenuation rate, indicating that a 1:2 mass ratio is beneficial for balancing UV aging stability and thermo-oxidative aging stability.

[0143] according to Figure 3 The bar chart showing the elongation attenuation rate of sheath layer 3 after 1000 hours of UV irradiation shows that the bar heights of Examples 1-4 are significantly lower than those of Comparative Examples 1-7. Figure 3 It can demonstrate the synergistic UV resistance effect of surface-modified titanium dioxide / zinc oxide composite particles or surface-modified cerium oxide particles with antioxidant 1010, among which Example 1 has the lowest elongation attenuation rate.

[0144] Test Example 3:

[0145] This test example evaluates the ozone barrier performance of sheath layer 3 in a weather-resistant and high-temperature-resistant polyether-based TPU robot cable, and includes the following steps:

[0146] (1) Take the cables prepared in Examples 1-4 and Comparative Examples 1-7 respectively, peel off the sheath layer 3 and prepare a diaphragm sample with a thickness of 1.0 mm.

[0147] (2) Install the membrane sample in the ozone permeation test fixture, and let ozone gas pass through one side of the membrane sample. The ozone concentration is 50 ppm, the test temperature is 40℃, and the relative humidity is 65%.

[0148] (3) High-purity nitrogen gas was introduced into the other side of the membrane sample as a carrier gas, and the ozone concentration on the permeate side was continuously detected by an ozone detector for 72 hours.

[0149] (4) Calculate the ozone permeability based on the effective permeation area, sample thickness, test time and ozone concentration difference.

[0150] (5) Using the ozone permeability of Comparative Example 1 as a benchmark, calculate the ozone permeability reduction rate.

[0151] Table 3. Ozone permeability test results of sheath layer 3

[0152] sample Ozone permeability (×10⁻¹³ cm³·cm / (cm²·s·Pa)) The reduction rate (%) compared to control example 1 Example 1 0.24 91.6 Example 2 0.31 89.2 Example 3 0.21 92.7 Example 4 0.36 87.4 Comparative Example 1 2.86 0 Comparative Example 2 1.18 58.7 Comparative Example 3 0.79 72.4 Comparative Example 4 0.88 69.2 Comparative Example 5 1.02 64.3 Comparative Example 6 1.64 42.7 Comparative Example 7 3.47 -21.3

[0153] in conclusion:

[0154] According to the data in Table 3, the ozone permeability of Examples 1 and 3 decreased by 91.6% and 92.7% respectively compared to Comparative Example 1, indicating that the high-density molding of the sheath layer 3 can effectively reduce the ozone diffusion channels. The density of the sheath layer 3 in Comparative Example 6 is 1.18 g / cm³. 3 The micropores in Example 2 have a diameter of 84 nm, and their ozone permeability is significantly higher than that of Example 1, indicating that insufficient die pressure and improper temperature settings can lead to a decrease in the density of the sheath layer 3. Comparative Example 2, without the addition of surface-modified titanium dioxide / zinc oxide composite particles, has an ozone permeability higher than that of Example 1, indicating that the surface-modified titanium dioxide / zinc oxide composite particles participate in the formation of the barrier structure in the sheath layer 3. Example 4, even with surface-modified cerium oxide particles, still exhibits a low ozone permeability, indicating that the surface-modified cerium oxide particles can maintain the ozone barrier effect of the sheath layer 3.

[0155] according to Figure 4 The ozone permeability graph of the sheath layer 3 shown in the figure indicates that the data points corresponding to Examples 1 to 4 are in the low permeability range, while the data points of Comparative Examples 1, 6 and 7 are in the high permeability range. Figure 4 It can demonstrate the impact of sheath layer density, micropore diameter, and particle dispersion state on ozone barrier performance.

[0156] Test Example 4:

[0157] This test case evaluates the durability of weather-resistant and high-temperature-resistant polyether-based TPU robot cables under repeated bending conditions at robot joints, and includes the following steps:

[0158] (1) Take the cables prepared in Examples 1-4 and Comparative Examples 1-7 respectively, and cut a sample with a length of 1.5m.

[0159] (2) The sample is installed on the robot joint bending tester. The bending radius is set to 6 times the outer diameter of the cable, the bending angle is ±180°, and the bending frequency is 30 times / min.

[0160] (3) During the test, observe the surface condition of the sheath layer 3 after every 200,000 bending cycles and test the DC resistance of the conductive core wire 1.

[0161] (4) When any of the following occurs: a through crack in the sheath layer 3, a break in the conductive core wire 1, or a change in the DC resistance of the conductive core wire 1 exceeding 10%, it shall be recorded as a failure. Samples that do not exhibit the above conditions shall be continuously tested up to 2 million times.

[0162] (5) Calculate the rate of change of DC resistance of conductive core wire 1 according to the following formula: Rate of change of DC resistance of conductive core wire 1 = (DC resistance after bending - initial DC resistance) / initial DC resistance × 100%.

[0163] Table 4. Results of Robot Joint Bending Durability Test

[0164] sample When the sheath layer reaches 2 million cycles, it reaches state 3. Failure cycle count (in ten thousand times) DC resistance change rate of conductive core wire 1 (%) Example 1 No cracks Not expired 2.8 Example 2 No through cracks Not expired 3.6 Example 3 No cracks Not expired 2.4 Example 4 Slight indentation, no through cracks Not expired 4.1 Comparative Example 1 Fine cracks 168 7.9 Comparative Example 2 Surface cracks 152 8.7 Comparative Example 3 Surface cracks 176 7.1 Comparative Example 4 Fine cracks 181 6.8 Comparative Example 5 Localized cracks 164 8.2 Comparative Example 6 Through crack 137 9.6 Comparative Example 7 Through crack 94 12.8

[0165] in conclusion:

[0166] According to the data in Table 4, Examples 1-4 all completed 2 million robot joint bending tests. No through-cracks appeared in the sheath layer 3, and the DC resistance change rate of the conductive core wire 1 was controlled within 4.1%. Comparative Example 6, due to insufficient densification of the sheath layer 3, developed through-cracks after 1.37 million bending cycles; Comparative Example 7, due to insufficient flexibility and heat aging resistance of the PVC material, failed after 940,000 bending cycles. These results indicate that the sheath layer 3 formed by polyether-based TPU, under the action of axial orientation and three-dimensional network structure, can maintain elastic recovery and structural integrity during repeated bending. The addition of surface-modified titanium dioxide / zinc oxide composite particles or surface-modified cerium oxide particles and antioxidant 1010 did not weaken the flexibility of the sheath layer 3.

[0167] according to Figure 5 The bar chart showing the number of bending cycles of the robot joints indicates that Examples 1-4 all reached 2 million bending cycles, while the failure cycles of Comparative Examples 1-7 were significantly lower. Figure 5 This demonstrates the durability advantage of the cable of this invention in high-frequency bending environments of robot joints.

Claims

1. A weather-resistant and high-temperature resistant polyether-based TPU robot cable, characterized in that, It includes a conductive core wire, an insulating layer covering the conductive core wire, and a sheath layer covering the insulating layer; The sheath layer uses polyether-based TPU as the substrate, and the density of the sheath layer is 1.25 g / cm³. 3 above; The sheath layer contains surface-modified titanium dioxide / zinc oxide composite particles or surface-modified cerium oxide particles, as well as antioxidant 1010, wherein the mass ratio of the surface-modified titanium dioxide / zinc oxide composite particles or surface-modified cerium oxide particles to the antioxidant 1010 is 1:

2. The molecular chains of polyether-based TPU in the sheath layer are oriented along the cable axis and form a three-dimensional network structure through the urethane bonds contained in the polyether-based TPU itself. The insulation layer is made of high-density polyethylene, and the insulation layer and the sheath layer are bonded together by a co-extrusion process.

2. The weather-resistant and high-temperature resistant polyether-based TPU robot cable according to claim 1, characterized in that, The surface-modified titanium dioxide / zinc oxide composite particles are prepared from nano-titanium dioxide, nano-zinc oxide and γ-aminopropyltriethoxysilane.

3. The weather-resistant and high-temperature resistant polyether-based TPU robot cable according to claim 2, characterized in that, The mass ratio of the nano-titanium dioxide to the nano-zinc oxide is 40:60 to 60:

40.

4. The weather-resistant and high-temperature resistant polyether-based TPU robot cable according to claim 1, characterized in that, The surface-modified cerium oxide particles were prepared from nano-cerium oxide and γ-aminopropyltriethoxysilane.

5. The weather-resistant and high-temperature resistant polyether-based TPU robot cable according to claim 1, characterized in that, The average particle size of the surface-modified titanium dioxide / zinc oxide composite particles or the surface-modified cerium oxide particles is less than 100 nm.

6. The weather-resistant and high-temperature-resistant polyether-based TPU robot cable according to claim 1, characterized in that, The amount of antioxidant 1010 added is 0.5% to 1% of the mass of the polyether-based TPU.

7. The weather-resistant and high-temperature resistant polyether-based TPU robot cable according to claim 1, characterized in that, The sheath layer has micropores with a diameter of less than 50 nm.

8. The weather-resistant and high-temperature resistant polyether-based TPU robot cable according to claim 1, characterized in that, The sheath layer is a sheath layer obtained by the following steps: Based on 100 parts by weight of the polyether-based TPU, 0.25 to 0.50 parts by weight of the surface-modified titanium dioxide / zinc oxide composite particles or the surface-modified cerium oxide particles, and 0.50 to 1.00 parts by weight of the antioxidant 1010 are added. After mixing, the mixture is extruded using a two-stage screw extruder, wherein the temperature of the first zone is 180 to 190°C, the temperature of the second zone is 160 to 170°C, and the die pressure is 8 to 10 MPa.

9. The weather-resistant and high-temperature-resistant polyether-based TPU robot cable according to claim 8, characterized in that, After extrusion, the sheath layer is traction-shaped along the cable axis at a traction ratio of 1.05 to 1.20, so that the molecular chains of polyether-based TPU in the sheath layer are oriented along the cable axis.

10. The weather-resistant and high-temperature-resistant polyether-based TPU robot cable according to claim 1, characterized in that, The conductive core wire is formed by stranding multiple annealed copper wires. The diameter of a single strand of the multiple annealed copper wire is 0.08 to 0.15 mm, and the stranding pitch is 8 to 14 times the outer diameter of the conductive core wire.